The effects of socioeconomic status on baseline neurocognitive testing scores. Issue 3 (3rd July 2021) - Rexrode, Briana L.; Armstrong, Jennifer L.; Hallberg, Christopher T.; Copeland, Benjamin W.; Bradney, Debbie A.; Bowman, Thomas G.
Abstract: Baseline neurocognitive testing has been recommended to provide a more accurate representation of the pre-concussion cognitive status of individual athletes. Socioeconomic status is not typically controlled for when obtaining baseline scores, which may lead to inaccurate findings if post-injury scores are compared to normative data. Understanding the role of socioeconomic status in baseline testing is important for the accurate analysis of test scores and proper evaluation of patients if individualized baseline data are not available. Our purpose was to investigate the effects of socioeconomic status, as determined by eligibility for free or reduced cost lunch on baseline neurocognitive test scores in secondary school athletes. 1, 788 secondary school athletes (females = 778, males = 1, 010, age = 14.96 ± 1.11 years, height = 171.25 ± 17.83 cm, mass = 66.82 ± 21.63 kg) completed the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) upon starting scholastic athletics. ImPACT components (symptom severity scores and composite scores of verbal memory, visual memory, visual motor speed, and reaction time) served as the dependent variables. School administration coded free or reduced cost lunch eligibility ( N  = 1255 not eligible, N  = 563 eligible) for each participant (group), which served as the independent variable. Free or reduced cost lunch eligibility significantly altered the combined dependent variables (multivariate F 5, 1780 =14.41, p  < .001, ɳ 2 = .04) when sex and age were controlled. Follow up ANOVAs showed that participants eligible for free or reduced cost lunch scored significantly worse on verbal memory ( F 1, 1784 = 24.81, p  < .001, ɳ 2 = .01), visual memory ( F 1, 1784 = 24.90, p  < .001, ɳ 2 = .01), and visual motor speed ( F 1, 1784 = 50.54, p  < .001, ɳ 2 = .03). In addition, slower reaction times ( F 1, 1784 = 35.10, p  < .001, ɳ 2 = .02) and higher symptom severity scores ( F 1, 1784 = 10.37, p  < .01, ɳ 2 = .01) were observed in those eligible for free or reduced cost lunch. If normative data are used instead of individual baselines, potential modifiers such as socioeconomic status should be taken into account when analyzing concussion scores to provide accurate diagnoses.